Sistem Pengendalian Internal Atas Dana Desa: Analisis COSO Framework 2013 - Sriyanto, Darmawan; Harsono, Subambang; Chairina, Chairina (Universitas Islam Islam Sumatera Utara, 2023)
Implementing an internal control system in managing village funds is important considering that the priority objective of managing village funds is to increase development and empower village communities. Therefore, this research focuses on the implementation of the internal control system carried out by village government officials by referring to the internal control system theory established by COSO and by looking at the suitability of existing policies in the field. The objects of this research are Ramunia 1 Village and Beringin Village, Deli Serdang subdistrict, using a postpositivist approach with descriptive methods. The results of this research show that not all components of the internal control system by COSO have been implemented by Ramunia 1 Village and Beringin Village. The problem that is the main concern is due to the village government's lack of understanding regarding internal control in managing village funds, policy socialization from the central government which has not yet fully socialized the internal control system policy to the village government